2015
DOI: 10.6018/analesps.31.2.172151
|View full text |Cite
|
Sign up to set email alerts
|

Andar como forma de ejercicio físico en la Fibromialgia: un estudio de identificación de creencias desde la Teoría de la Acción Planeada

Abstract: Título: Andar como forma de ejercicio físico en la Fibromialgia: un estudio de identificación de creencias desde la Teoría de la Acción Planeada. Resumen Este estudio corresponde a la primera fase de investigación formativa recomendada en la teoría de la Acción Planeada para desarrollar una intervención. Nuestros objetivos son identificar las creencias modales sobre la realización de una pauta de ejercicio en personas con fibromialgia, probar los ítems para la evaluación directa de los constructos predictivos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
14
0
3
Order By: Relevance
“…Measures assessing behaviour-specific control beliefs may offer a better alternative (Norman, 1995), although few such measures are currently available (e.g., Goldman, Greenbaum, & Darkes, 1997; Pastor et al, 2015). Further, owing to their highly behaviour-specific content, the few existing measures may be inappropriate for assessing other domains of health behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Measures assessing behaviour-specific control beliefs may offer a better alternative (Norman, 1995), although few such measures are currently available (e.g., Goldman, Greenbaum, & Darkes, 1997; Pastor et al, 2015). Further, owing to their highly behaviour-specific content, the few existing measures may be inappropriate for assessing other domains of health behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a better understanding of these behaviors and health outcomes in chronic pain, some authors have recommended the investigation of the role of motivational and affective factors from a self-regulation perspective (Vlaeyen and Morley, 2004, 2009; Van Damme and Kindermans, 2015). Research on this issue in fibromyalgia is scarce despite its relevance given the patients’ heterogeneity and high prevalence of both avoidance and persistence activity patterns (Van Koulil et al, 2008), the high disabling impact of the problem, the reported low rates of physical activity (McLoughlin et al, 2011; López-Roig et al, 2016), and the perceived difficulties in performing regular physical activity (Pastor et al, 2015; Peñacoba et al, 2017). Our study tested the Karsdorp and Vlaeyen (2011) affect-goals interaction hypothesis, but in a specific chronic pain sample consisting of women with fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…This is not typically reported in the literature. For example, a number of belief-elicitation studies have been published on a variety of behaviors, such as stress management (Yzer & Gilasevitch, 2019), walking among women with fibromyalgia (Pastor et al, 2015), African American caregivers' decision to give sugary drinks to their preschoolers (Tipton, 2014), and Hispanic mothers' beliefs about having their daughters take the HPV vaccine (Roncancio, Ward, Carmack, Muñoz, & Cribbs, 2017). While all of these studies have value, they only present the results of what beliefs were elicited about the behavior, and not which beliefs would be best to use to promote behavior change.…”
Section: Discussionmentioning
confidence: 99%